Measuring quality of life in elderly populations: a review of instruments used - Maryam Nikkhah; Majideh Heravi-Karimooi; Nahid Rejeh; Hamid Sharif Nia; Ali Montazeri (Payesh, 2017)
Objective (s): Due to the increasing elderly population in the world, need to access accurate data for planning and action to protect and promote the health of the elderly is more attention. Choosing right tools with good psychometrics properties is a prerequisite for access accurate data. The aim of this systematic review was to assess the common tool used measuring quality of life. Methods: A comprehensive search of databases of Pubmed, Medline, and Science Direct was conducted, using the related keywords to development and psychometrics of older quality of life instruments. Results: In all a total of 342 papers were included in this review. Most commonly used quality of life measures in elderly were generic instruments (81.3%). Among generic measures the 36-Item Short Form Health Survey (SF-36) was widely used (26.8%), while only specific tools to measure quality of life in elderly people accounted for 18.7%. Among specific measures the World Health Organization Quality of Life - OLD was widely used (9.6%). Conclusion: The results revealed that CASP-19, OPQOL-BRIEF and WHOQOL-AGE are the best specific measures that can be recommended for measuring quality of life in elderly populations.